Understanding the impact of the COVID-19 pandemic on HIV/AIDS care and management in Tanzania: challenges, adaptations and lessons learnt-a review - Epafra Luka Mwanja; Mansour Maulid Mshenga; Alex Philemon Alexander; Margareth Stewart Makuchilo; Kheri Mwijage Kagya; Kololo Sidney Otladisa (BMJ Publishing Group, 2024)
This review examines the impact of the COVID-19 pandemic on HIV/AIDS care and management in Tanzania, highlighting challenges, adaptations and lessons learnt. The pandemic has led to disruptions in service delivery, reduced access to testing and treatment, and increased stigma and discrimination. Adaptations and innovations, such as telemedicine (telehealth and virtual care), multimonth dispensing of antiretroviral therapy, decentralised drug distribution initiatives, have been implemented to mitigate the challenges faced in HIV/AIDS care and management. Integration of HIV/AIDS and COVID-19 services is crucial to ensure the continuity of care and management in the postpandemic by strengthening healthcare systems, improving supply chain management and enhancing community engagement.